Adaptive Fuzzy-PI for Induction Motor Speed Control - Maghfiroh, Hari; Slamet Saputro , Joko; Fahmizal, Fahmizal; Ahmad Baballe , Muhammad (Peneliti Teknologi Teknik Indonesia, 2023)
An induction motor (IM) is one type of AC motor which widely used. IM is chosen due to its simplicity, reliability, efficiency, and low cost. There are many methods proposed to control the speed of IM which is known as variable speed drive (VFD). In this study, the DTC method is used since it is more robust to the parameter’s changes. The combination of the Fuzzy and PI method is used in speed control. PID performances decrease when the system condition changes. Therefore, fuzzy is used as an adaptive algorithm to vary the PID gain. It was superior in terms of settling time, overshoot/ undershoot, and IAE compared to the PI method. It has lower IAE in both speed tracking and loaded conditions by 44.98% and 4.47%, respectively.